Spectrum adequacy of antibiotic regimens for secondary peritonitis: a retrospective analysis in intermediate and intensive care unit patients. Issue 1 (December 2015) - Steinbach, Cathérine; Töpper, Christoph; Adam, Thomas; Kees, Martin
Abstract Background Secondary peritonitis requires surgical source control and adequate antimicrobial treatment. Antimicrobial regimens are usually selected according to local susceptibility data of individual pathogens against single agents, but this neglects both the polymicrobial nature of the infection and the use of combination therapy. We analysed the probability of common regimens to cover all relevant pathogens isolated in one patient ("spectrum adequacy rate", SAR) in a real-life data set. Methods Data from 242 patients with secondary peritonitis (88 community acquired, 154 postoperative cases) treated in our IMCU/ICU were obtained retrospectively. The relative frequency of pathogens, resistance rates and the SAR were analysed using the free software R. Results Enterococci were isolated in 47.1 % of all patients, followed byEscherichia coli (42.6 %), other enterobacteriaceae (33.1 %), anaerobes (29.8 %) andCandida spp. (28.9 %). Resistance patterns were consistent with general surveillance data from our hospital. The susceptibility rates and SAR were lower in postoperative than in community acquired cases. The following regimens yielded a SAR > 95 % when enterobacteriaceae only were considered: piperacillin/tazobactam + gentamicin, cefotaxim (only for community acquired cases), cefotaxim + gentamicin, meropenem, tigecycline + gentamicin or tigecycline + ciprofloxaxin. When enterococci were also considered, all betalactam based regimens required combination with vancomycin or linezolid for a SAR > 95 %, whereas TGC based regimens were not compromised. As forCandida spp., the SAR of fluconazole was 81.9–87.5 %. Conclusions This study demonstrates a rational approach to assess the adequacy of antimicrobial regimens in secondary peritonitis, which may help to adjust local guidelines or to select candidate regimens for clinical studies.